Knowledge and nutrition-related practices among caregivers of adolescents with sickle cell disease in the Greater Accra region of Ghana - Ohemeng, A.; Nartey, E.B.; Quaidoo, E.; Ansong, R.S.; Asiedu, M.S. (BMC Public Health, 2023)
Background Due to its severe adverse effect on child mortality, sickle cell disease (SCD) has been identified as a set of diseases of public health concern. The high mortality rate among children with SCD in Africa has been attributed to several factors including sub-optimal management and care. This study documented the nutrition-related knowledge and practices of caregivers of teenagers who suffer from sickle cell disease (SCD) to inform decisions on integrated management of the disease. Methods The study included caregivers (n=225) of adolescents with SCD who attended clinic at selected hospitals in Accra, Ghana. Pre-tested semi-structured questionnaire was employed in the gathering of information related to general and nutrition-related knowledge about SCD, as well as data on their nutrition-related practices with regards to their children who suffer from SCD. Pearson’s Chi-square test and binary logistic regression analyses were applied to explore the relationship between caregivers’ nutrition-related knowledge and practice. Results Nutrition-related knowledge among the caregivers studied was low, with less than a third of them (29.3%) of the sample being classified as having good knowledge. Caregivers who considered nutrition care when the child experienced crises were few (21.8%), and those with low nutrition-related knowledge were less likely to do this compared with caregivers having high knowledge (OR=0.37, 95% CI=0.18, 0.78). The common nutrition actions reported were the provision of more fruits/fruit juices (36.5%) and warm fluids such as soups and teas (31.7%). More than a third of the caregivers (38.7%) admitted that they faced challenges in caring for their adolescents with SCD, particularly in the area of finance for the needed health care. Conclusion Our study findings indicate that it is important to incorporate appropriate nutrition education messages for caregivers as part of a holistic management of SCD.
Research Article
Keywords: Sickle cell disease; Nutrition-related; Caregivers; Adolescents; Ghana; Nutrition practices